2011
DOI: 10.1111/j.1524-4741.2011.01162.x
|View full text |Cite
|
Sign up to set email alerts
|

Methotrexate in the Management of Idiopathic Granulomatous Mastitis: Review of 108 Published Cases and Report of Four Cases

Abstract: This study aimed to discuss the role of agents, such as steroids and methotrexate (MTX), in the treatment of patients with idiopathic granulomatous mastitis (IGM). Using Pubmed and Google Scholar data bases, a retrospective study was carried out on IGM cases treated with steroids and/or MTX between 1972 and 2010. Four IGM cases treated with MTX at our clinic were also summarized in this study. A total of 541 IGM cases since 1972, including ours, were retrospectively analyzed. Steroid treatment 5-85 mg was admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
100
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 47 publications
4
100
1
4
Order By: Relevance
“…However, the granulomatous mastitis relapsed when the dose of prednisolone was tapered to 15 mg/day. It has been reported that a low weekly dose of MTX may be effective in cases with resistance to corticosteroids (5,12). Therefore, MTX was added to the patient's therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, the granulomatous mastitis relapsed when the dose of prednisolone was tapered to 15 mg/day. It has been reported that a low weekly dose of MTX may be effective in cases with resistance to corticosteroids (5,12). Therefore, MTX was added to the patient's therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Corticosteroid therapy in IGM is increasingly used (26)(27)(28). Further studies looking into the impact of immunomodulator treatment in cases of granulomatous breast infections are needed, with particular caution if combined with an antimicrobial regime that includes rifampin (29).…”
Section: Discussionmentioning
confidence: 99%
“…Several other reports of using 60 mg/kg/day prednisolone to treat IGM have also been published. However, in the literature the recommended dose ranges between 0.5 and 2 mg/kg/day (11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%